Pengaruh Pemberian Tugas Secara Kelompok Terhadap Prestasi Belajar Matematika Pada Siswa SMP - Herlawan Herlawan; Deby Alsah (Jurnal Akademik Pendidikan Matematika, 2022)
This study aims to determine the effect of group assignments on mathematics learning achievement in seventh grade students of SMP Negeri 8 Buton. This research is a quantitative research with a quasi-experimental method (quasi-experimental) carried out at SMP Negeri 8 Buton Tengah. The population in this study was class VII which consisted of 2 classes. The sample in this study were students of class VIIA as the experimental class and students of class VIIB as the control class, totaling 37 students. The instrument used in this research is a test of learning outcomes and documentation of learning outcomes. The results of the descriptive analysis were obtained: (1) the average initial test data for the experimental class mathematics learning achievement was 38.61, the final test data average for the experimental class mathematics learning achievement was 82.78 and the experimental class mathematics learning achievement increased 44.17 . (2) based on the results of hypothesis testing, it can be seen that tcount = 5.333 with df = 34 and significant (2-tailed) = 0.000 <0.05, so it can be concluded that H0 is rejected and H1 is accepted. So it was concluded that the use of the group assignment method had an effect on mathematics learning achievement in class VII students of SMP Negeri 8 Buton Tengah.